Prevalence of preterm newborn born at the León Becerra Camacho Hospital: PERIOD 2016-2023. CITY OF MILAGRO-ECUADOR - Balcázar Quimi, Wilman; Dalila Barros, Alicia; Merchán, Carla Sampedro; Chancay, George Soledispa; Balcázar Martínez, Wilman (REDIELUZ, 2024)
The neonatology area of ​​the León Becerra Camacho Hospital in the Milagro canton, of which we are a part, has considered making this publication given our situation as it is the reference hospital in the rural area of ​​the province of Guayas in order to reflect the events related to neonatology in our environment. Hence our motivation for this article taking as the population to study premature babies born in our hospital who have been hospitalized in the period 2016 to 2022. This publication attempts, using a scientific and statistical basis, to provide information about the reality of the incidence of preterm newborns in the Milagro Canton. Preterm births are equivalent to more than 1 in 10 births. In 2019, approximately 900,000 children died worldwide as a result of complications related to premature birth, the main ones being sepsis and hyaline membrane disease. This study is retrospective, longitudinal, descriptive, quantitative, non-experimental, in which the records of premature newborns from 2016 to 2022 were analyzed and subsequent tabulations were analyzed to obtain corresponding percentages. Among the results found we have 527 preterm hospital admissions in the referred period. The most relevant complication was Sepsis (40%). 77.2% were discharged alive, 8.15% have been transferred to third level units, and 14.6% died.